2010
DOI: 10.1002/ardp.201000002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Quinoline Derivatives as Inhibitors of Human Tumor Cells Growth

Abstract: A series of new 8-[(2H-tetrazol-5-yl)methoxy]quinoline derivatives, their sugar hydrazones, and their N-glycoside derivatives were synthesized. Furthermore, the 1,2,4-triazole-3-one derivatives 3 and 4 were synthesized from the amidrazone derivative 2. Some of the newly prepared compounds demonstrated inhibitory effects on the growth of MCF-7 human breast cancer cells as compared with the activity of the commonly used anticancer drug, cisplatin. The results of antitumor evaluation revealed that compounds 2-5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 35 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, the 4,6‐bis(4‐chlorophenyl)‐2‐(2,3,4,5,6‐pentahydroxyhexylidene) hydrazinyl)‐nicotinonitriles ( 17 ) was prepared by heating compound 6 with D ‐glucose (Scheme ). The formed product revealed absorption frequencies due to OH, NH, CN, and C═N in IR spectrum and its 1 H NMR spectrum showed the presence of the sugar protons, NH, and azomethine (CH═N) . Acetylation of the hydrazone derivative 17 by heating in acetic anhydride gave its corresponding O ‐acetylated sugar hydrazone derivative 18 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the 4,6‐bis(4‐chlorophenyl)‐2‐(2,3,4,5,6‐pentahydroxyhexylidene) hydrazinyl)‐nicotinonitriles ( 17 ) was prepared by heating compound 6 with D ‐glucose (Scheme ). The formed product revealed absorption frequencies due to OH, NH, CN, and C═N in IR spectrum and its 1 H NMR spectrum showed the presence of the sugar protons, NH, and azomethine (CH═N) . Acetylation of the hydrazone derivative 17 by heating in acetic anhydride gave its corresponding O ‐acetylated sugar hydrazone derivative 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Our data reveal that propofol increased SOD levels but decreased GPx and CAT levels in GBM 8401 cells. Previous studies have shown that quinoline derivatives induced the oxidative stress by increasing SOD activities but decreasing CAT and GPx activities, accompanied by a high production of H 2 O 2 which caused human breast cancer cell death . Therefore, this study implies that activities of GPx and CAT (H 2 O 2 ‐detoxifying enzymes) decreased with propofol, while activities of SOD (a O2‐converting enzyme) increased with propopol which possibly led to H 2 O 2 accumulation and subsequently caused GBM 8401 cell death.…”
Section: Discussionmentioning
confidence: 60%
“…Keeping above in mind, we decided to synthesize conjugates of the above-mentioned moieties to study the biological profile of the resulting product. Genesis of our chemistry is derived from the fact that few earlier conjugates of 1,2,4-triazole and quinoline, where these molecules are linked via oxygen-or amide-containing linkers in a single frame, are known to possess biological activities like antimalarial 34 , antimicrobial 35 , anti tubercular 36 , antitumor 37,38 and antiviral 39 . However, the literature data about molecules that contain both of these bioactive ligands directly linked/bonded to each other in a single molecular frame are unknown.…”
Section: Introductionmentioning
confidence: 99%